Helminths and COVID-19 susceptibility, disease progression, and vaccination efficacy. Issue 4 (April 2022) - Whitehead, Bradley; Christiansen, Simon; Østergaard, Lars; Nejsum, Peter
Abstract : Almost 2 years into the coronavirus disease 2019 (COVID-19) pandemic, it remains to be determined how helminths interact with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We discuss how helminths may alter susceptibility to infection, COVID-19 pathology, and the efficiency of vaccines by combined analysis of available COVID-19 data and previous investigations of the effect of helminths in viral infections.